Development of Yellow Sweet Potato and Red Kidney Bean-based Instant Cream Soup for Pregnant Mothers with Chronic Energy Deficiency - Fahrul Rozi; Sri Anna Marliyati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
This study aimed to develop an instant cream soup formula composed of yellow sweet potato and red kidney bean for maternal chronic energy deficiency. The selected formula is acceptable based on organoleptic test. In addition, the food formula is expected to meet nutritional needs, including protein, fat, carbohydrate, energy, and vitamin A. Amino acid score and in vitro protein digestibility were also measured to verify whether or not the product of the formulation has high protein quality. The instant cream soup was composed of yellow sweet potato and red kidney bean. Additional ingredients that were added to increase the nutritional value and sensoryattributes of the instant cream soup included soy protein isolate, egg white flour, maltodextrin, red palm oil, onion, garlic, leek, celery, chicken broth, fresh cream (cooking cream), black pepper, and salt). This experimental study used a randomized factorial design in laboratory. The treatment unit included two factors: provision of yellow sweet potato and red kidney bean consisting of three levels (50%:50%, 75%:25%, and 25%:75%) and addition of maltodextrin consisting of two levels (0% and 5%). Hedonic organoleptic analysis showed that theselected formula comprised 75%:25% yellow sweet potato and red kidney bean and 5% maltodextrin addition (F5). Nutrient content analysis revealed that the product contained 3.85% moisture, 3.15% ash, 30.19% protein, 14.18% fat, 48.63% carbohydrate, 443 kcal energy, 17.67% dietary fiber, 87 ppm β-carotene, and 77.21% protein digestibility. This study also showed that methionine and cysteine were the limiting amino acids in the selected product with a score of 47%. Acceptability from 100 pregnant women was assessed, and results showed that 87% of pregnant women accepted the product. These results indicate that this product has the potential to be an alternative snack for maternal chronic energy deficiency because of its nutritional values.